2011
DOI: 10.1037/h0094007
|View full text |Cite
|
Sign up to set email alerts
|

Mouth versus eyes: Gaze fixation during perception of sung interval size.

Abstract: We used eye tracking to examine the relative influence of the mouth and eyes on perception of sung interval size. Frequency and duration of gaze were tracked while participants rated the size of intervals produced by two singers in three signal-to-noise conditions, corresponding to high, medium and low audibility. All intervals ascended in pitch direction and ranged in size from 0 to 12 semitones. Both the frequency and duration of gaze fixations revealed that the mouth was the most salient aspect of the visua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…Participants’ ratings were also significantly correlated with the actual interval size in the V condition ( r = 0.60, p < 0.0001). Results of the V condition corroborate previous studies on judgments of visual interval size [ 10 , 21 ]. Ratings in the C condition were also significantly correlated with the actual interval size as seen and heard in the stimulus ( r = 0.889, p < 0.001).…”
Section: Resultssupporting
confidence: 88%
“…Participants’ ratings were also significantly correlated with the actual interval size in the V condition ( r = 0.60, p < 0.0001). Results of the V condition corroborate previous studies on judgments of visual interval size [ 10 , 21 ]. Ratings in the C condition were also significantly correlated with the actual interval size as seen and heard in the stimulus ( r = 0.889, p < 0.001).…”
Section: Resultssupporting
confidence: 88%
“…However, studies completed with adults have shown that the length of attention to singers' facial cues is related to the complexity of the auditory stimuli. Russo, Sandstrom, and Maksimowski (2011) found that adults looked longer at the mouth of a singer when sung intervals were presented in combination with other auditory information than in isolation. That an increase in the amount of auditory information resulted in longer attention to the singer's facial cues may help explain infants' longer attention to singing than to speech in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Employing a similar eye movement strategy in the dynamic face recognition task may result in similar behavioral results as the static face recognition study, with higher sensitivity in recognizing the more familiar East Asian and Western Caucasian faces than African faces (Tan et al., 2012). However, previous face-processing studies involving dynamic stimuli in naturalistic settings have revealed a different eye movement strategy, with more fixations directed toward the mouth (e.g., Pillai et al., 2012; Russo et al., 2011; Vo et al., 2012). Therefore, it is plausible that Malaysian Chinese participants’ fixation pattern may be different when viewing dynamic stimuli, as facial movements may redirect participants’ attention to features that may contain more useful visual information.…”
mentioning
confidence: 90%
“…Therefore, utilizing static stimuli may not be an accurate representation of real-life situations and, as a result, may not yield similar recognition performance as recognizing dynamic faces, which requires observers to encode information unique to a face in order to distinguish it from other faces despite possible transformation of stimuli or a change of perspective and presentation method (Hill, Schyns, & Akamatsu, 1997; Hockley, Hemsworth, & Consoli, 1999; O’Toole et al., 2006; Read, Vokey, & Hammersley, 1990; Valentin, Abdi, & Edeleman, 1999). Additionally, face-processing studies have found that observers employ different eye movement strategies, with attention directed toward the lower regions of the face, when perceiving dynamic stimuli (Pillai, Sheppard, & Mitchell, 2012; Russo, Sandstrom, & Maksimowski, 2011; Vo, Smith, Mital, & Henderson, 2012). Thus, it is plausible that observers may adopt a strategy different from those previously reported in static face recognition studies when instructed to recognize dynamic faces.…”
mentioning
confidence: 99%